Correlation Between Knowledge and Attitude with Practice Toward Hypertension in The Community of Sidikalang District in Dairi Regency - Justin, Chris Audric; Ahmad, Herwindo; Arrasyid, Nurfida Khairina; Nasution, Afrida Aryani (TALENTA Publisher, Universitas Sumatera Utara, 2024)
Background: Hypertension contributes to 71% of deaths in the world and 85% of them are found in developing countries. In Indonesia, it is reported that 91.3 million people suffer from hypertension which contributes to 35% of deaths of the population in Indonesia. The high incidence of hypertension is known to be closely related to a lack of knowledge and attitudes toward hypertension. Therefore, it is necessary to know the relationship between knowledge, attitudes and prac, tices toward hypertension. Method: This study used a cross-sectional research design. The sample in this study was the people of Sidikalang District who met the inclusion and exclusion criteria. The data used is primary data obtained using a questionnaire instrument and using the consecutive method. Results. Test results Chi-Square showed that there was no relationship between age (p>0.05), gender (p>0.05), and education (p>0.0.5) on knowledge and attitudes towards hypertension. Age (p=0.304) and education (p=0.150) showed there was no relationship with practice toward hypertension, and gender (and p=0.032) showed there was a relationship with practice toward hypertension. The level of knowledge (p=0.005) and attitude (p=0.000) show that there is a relationship with practice toward hypertension. Conclusion: There is a relationship between knowledge and attitude with practice toward hypertension in the Sidikalang District community.